Research productivity of agricultural scientists: Evidences from high performing and low performing institutes - PAUL, S; VIJAYARAGAVAN, K; SINGH, PREMLATA; BURMAN, R R (The Indian Journal of Agricultural Sciences, 2015)
The ever growing concern over enhancing research effectiveness of the public agricultural research system of the country has entailed the crucial need for assessing current status of research productivity. The sample of the study comprised of randomly drawn two hundred agricultural scientists across strata from a high performing and a low performing agricultural institute of India. A research productivity index was developed to measure productivity of respondents under study. The statistical analysis was based upon self-reported data by the scientists under different productivity parameters. The study revealed that there is ample scope of enhancing research productivity among the scientists as the majority (63.5%) of scientists had low to very low level of productivity. In the low performing institute, only 5% of the scientists had higher level of productivity. Even in the high performing institute, only 28% of the scientists had high to very high level of productivity. The findings of the study further indicated the crucial need for revisiting the present system of career advancement for Principal Scientists as the results of a t-test failed to produce a significant value of productivity difference between the Principal Scientists and Senior Scientists. Balanced involvement of the scientists from the low performing institute in research and teaching activities, organization development interventions in regular intervals for ensuring a pro-research and creative organizational environment and allocation of sufficient fund for individual research projects may be suggested among the necessary measures for harnessing optimum research productivity of scientists.